FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK UMKM - Rinaldi Zentira Fikri; Mourris Sagara; Didin Hadi Saputra; Nasuhi Nasuhi (JABE (Journal of Applied Business and Economic), 2020)
This study aims to examine the effect of taxpayer awareness, knowledge and understanding, and sanctions on MSME taxpayer compliance. The sample of this study was 80 respondents who were owners of micro, small and medium enterprises in Suralaga District, East Lombok Regency. The research results of this study were collected through a questionnaire which was processed and analyzed using the t test. The method used in determining the sample of this study is to use purposive sampling. The data quality test used in this study was the validity test of the Pearson correlation and the reliability test using Cronbach alpha. To test the hypothesis in this study using the t test. The results of this study indicate that all variabels have a significant effect such as taxpayer awareness, knowledge and understanding, tax sanctions have an effect on taxpayer compliance.